Washed microbiota transplantation improves patients with metabolic syndrome in South China - Wu, Lei; Lu, Xin-Jian; Lin, De-Jiang; Chen, Wen-Jia; Xue, Xing-Ying; Liu, Tao; Xu, Jia-Ting; Xie, Ya-Ting; Li, Man-Qing; Lin, Wen-Ying; Zhang, Qing; Wu, Qing-Ping; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Metabolic syndrome (MS) is a growing public health problem worldwide. The clinical impact of fecal microbiota transplantation (FMT) from healthy donors in MS patients is unclear, especially in southern Chinese populations. This study aimed to investigate the effect of washed microbiota transplantation (WMT) in MS patients in southern China. Methods: The clinical data of patients with different indications receiving 1-3 courses of WMT were retrospectively collected. The changes of BMI, blood glucose, blood lipids, blood pressure and other indicators before and after WMT were compared, such as fasting blood glucose (FBG), glycated hemoglobin (HbA1c), total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-c) ), high-density lipoprotein cholesterol (HDL-c), non-high-density lipoprotein (non-HDL-c), systolic blood pressure (SBP), diastolic blood pressure (DBP), etc. At the same time, comprehensive efficacy evaluation and atherosclerotic cardiovascular disease (ASCVD) grade assessment were performed on MS patients. Finally, 16S rRNA gene amplicon sequencing was performed on fecal samples of MS patients before and after transplantation. Results: A total of 237 patients were included, including 42 in the MS group and 195 in the non-MS group. For MS patients, WMT significantly improved the comprehensive efficacy of MS in short term 40.48% (p<0.001), medium term 36.00% (p=0.003), and long term 46.15% (p=0.020). Short-term significantly reduced FBG (p=0.023), TG (p=0.030), SBP (p=0.026) and BMI (p=0.031), and increased HDL-c (p=0.036). The medium term had a significant reduction in FBG (p=0.048), TC (p=0.022), LDL-c (p=0.043), non-HDL-c (p=0.024) and BMI (p=0.048). WMT had a significant short term (p=0.029) and medium term (p=0.011) ASCVD downgrading effect in the high-risk group of MS patients. WMT improved gut microbiota in MS patients. Conclusion: WMT has a significant improvement effect on MS patients and a significant downgrade effect on ASCVD risk in the high-risk group of patients with MS. WMT can restore gut microbiota homeostasis in MS patients. Therefore, the regulation of gut microbiota by WMT may provide a new clinical approach for the treatment of MS.